Towards high‐quality peri‐operative care: a global perspective. (5th January 2020) - Santhirapala, V.; Peden, C. J.; Meara, J. G.; Biccard, B. M.; Gelb, A. W.; Johnson, W. D.; Lipnick, M. S.; Makasa, E. M.; Martin, J.; Maswime, S.; Mellin‐Olsen, J.; McClain, C. D.
Summary: Article 25 of the United Nations' Universal Declaration of Human Rights enshrines the right to health and well‐being for every individual. However, universal access to high‐quality healthcare remains the purview of a handful of wealthy nations. This is no more apparent than in peri‐operative care, where an estimated five billion individuals lack access to safe, affordable and timely surgical care. Delivery of surgery and anaesthesia in low‐resource environments presents unique challenges that, when unaddressed, result in limited access to low‐quality care. Current peri‐operative research and clinical guidance often fail to acknowledge these system‐level deficits and therefore have limited applicability in low‐resource settings. In this manuscript, the authors priority‐set the need for equitable access to high‐quality peri‐operative care and analyse the system‐level contributors to excess peri‐operative mortality rates, a key marker of quality of care. To provide examples of how research and investment may close the equity gap, a modified Delphi method was adopted to curate and appraise interventions which may, with subsequent research and evaluation, begin to address the barriers to high‐quality peri‐operative care in low‐ and middle‐income countries.